Знахідки клинкової зброї ранньокелермеського часу з Українського Лісостепу - Шелехань, О.В. (Археологія і давня історія України, 2015)
У статті виділено та проаналізовано найбільш архаїчні зразки клинкової зброї скіфського типу з поховань на території Українського Лісостепу. В статье выделены и проанализированы наиболее архаичные образцы клинкового оружия скифского типа, которые происходят с территории Украинской Лесостепи. К ним отнесены экземпляры из курганов у с. Яснозорье, Медвин, Ленковцы и Рыжановка, датированные временем около середины VII в. до н. э. Показано, что их хронологическая позиция немного выше по сравнению с кавказскими аналогами. Это указывает на исходный характер последних. In the article the most archaic samples of blade weapon of Scythian type that originate from the territory of the Black Sea Forest-steppe were highlighted and analyzed. These are the specimens from the burial mounds near the villages Yasnozіryа, Medwyn, Lenkіvtsy and Ryzhanіvka that were dated by the time around the middle of the 7 century BC. It shows their slightly higher chronological position compared to Caucasian analogues and indicates the initial character of the latters.